2008
DOI: 10.1088/0953-8984/21/3/035401
|View full text |Cite
|
Sign up to set email alerts
|

Ground-state phase diagram of NaxCoO2: correlation of Na ordering with CoO2stacking sequences

Abstract: We have proposed a Hamiltonian that takes into account both Na-Na interactions and coupling between Na ions and CoO(2) layers. By a combination of the Monte Carlo and first-principles approaches, all the possible stacking sequences of CoO(2) layers together with the Na ordering have been obtained. In particular, an infinite series of ground states of Na ordering has been predicted in P3-Na(x)CoO(2). We have obtained the ground-state phase diagram with the variation of Na concentration, which explains well the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…63 The global instability index, a measure of the valence violations for the whole material, was plotted as a function of x, for O3-and P2-Na x CoO 2 and was found to be in good agreement with the formation energies obtained by Wang et al for these phases (shown in Figure 7a). 64 This study highlights the importance of lattice strains in explaining the highly unstable Na x MO 2 phases obtained at low Na content. 63 Challenges for Mn 3+ /Mn 4+ systems.-Manganese-based sodium-ion battery cathode materials fulfill the requirements for low cost, sustainable, and environmentally friendly energy storage technologies.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…63 The global instability index, a measure of the valence violations for the whole material, was plotted as a function of x, for O3-and P2-Na x CoO 2 and was found to be in good agreement with the formation energies obtained by Wang et al for these phases (shown in Figure 7a). 64 This study highlights the importance of lattice strains in explaining the highly unstable Na x MO 2 phases obtained at low Na content. 63 Challenges for Mn 3+ /Mn 4+ systems.-Manganese-based sodium-ion battery cathode materials fulfill the requirements for low cost, sustainable, and environmentally friendly energy storage technologies.…”
mentioning
confidence: 70%
“…The balance between all of these interactions is highly sensitive to sodium content, and various cationic distributions are observed for each composition along the electrochemical cycle. 67 64 This study used a combination of ab initio Density functional Theory (DFT) calculations within the Generalized Gradient Approximation (GGA) and Monte Carlo simulations to determine the ground state Na + ion/vacancy arrangements, as a function of x, for a variety of structural polytypes (O1, O2, O3, P2, and P3). The resulting 0 K phase stability diagram and the formation energies obtained for the lowest energy Na + ion/vacancy ordered arrangements, plotted as a function of x, are presented in Figure 7a.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The trial set consists of structures that commonly occur as ground-state orderings on the triangular lattice, such as those determined by Kaburagi and Kanamori [28] to be ground states with up to third-neighbor interactions, as well as the possible ground states for O3-NaCoO 2 found by Wang, Ding, and Ni [22]. In addition, potential structures are generated at Na concentrations of 1=4, 1=3, 1=2, 2=3, and 3=4.…”
Section: Methodsmentioning
confidence: 99%
“…Such Na-vacancy ordering occurs through clear first-order transitions in single TM compounds and therefore can be best studied in these systems. Though some work has been done on predicting alkali ion ordering in several Li-ion and Na-ion systems [21][22][23][24][25], this has been undertaken for the entire intercalation range in only a very few cases and with little comparison between similar systems.…”
Section: Introductionmentioning
confidence: 99%